Role of fermented dairy foods in human health - Kaur, Harpreet; Gupta, Taruna; Kapila, Suman; Kapila, Rajeev (Indian Journal of Dairy Science, 2020)
Unhealthy lifestyle and unbalanced diet are directly associated with diseases like inflammatory bowel diseases (IBD), diarrhea, hypersensitivity, irritable bowel syndrome, Helicobacter pylori infection, lactose intolerance, and gastroenteritis etc.The malfunction of the mediators of inflammation affect intestinal epithelial barrier functions by disruption of the physiological pathways. Fermented dairy foods influence human health through secretion of bioactive compounds and interaction of their inherent beneficial microbes with gut. Among all foods, fermented products have also been used as the most efficient vehicle for delivery of beneficial or probiotic microbes as they not only preferred by consumer being superior in sensory attributes during oral intake but also provide buffered media for survival of bacteria in harsh gastric environment.Â  In-vitro and in-vivo studies have shown that fermented dairy products (fermented milk, curd, yogurt, cheese, koumiss, paneer and kefir) assisted in the maintenance of normal mucosal homeostasis and modulate the immune response in a positive fashion which provides protection against various metabolic and pathogen mediated diseases by anti-oxidative, anti-microbial, anti-fungal, anti-inÃ»ammatory, anti-diabetic and anti-atherosclerotic activities. Cumulatively, this review focuses mainly on the health effects of fermented dairy foods.